2010
DOI: 10.2528/pierc10060202
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Epsilon Near Zero (Enz) Tunneling Circuit Using Microstrip Technology for High Integrability Applications

Abstract: Abstract-A novel compact Epsilon Near Zero (ENZ) tunneling circuit with microstrip coupling for high integrability applications is presented. Full design procedure, simulation and experimental results are shown, and a methodology to extract the effective permittivity and propagation constants in the tunnel is described. Detailed analysis of the dependence on external quality factor and tunnel to feed height ratio is investigated. Simulation and measurement results of the ENZ tunnel structure are in good agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…According to the previous section, in order to tunnel a single frequency, the condition h s h t must be satisfied [6]. Thus, a tunnel height h t = 0.4 mm was chosen.…”
Section: Epsilon Near Zero Tunnelmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the previous section, in order to tunnel a single frequency, the condition h s h t must be satisfied [6]. Thus, a tunnel height h t = 0.4 mm was chosen.…”
Section: Epsilon Near Zero Tunnelmentioning
confidence: 99%
“…Among these special material properties, near zero permittivity (also called Epsilon Near Zero) [5][6][7][8][9], and near zero permeability (known as Mu Near Zero) [10][11][12], have attracted much attention due to their potential applications at microwave frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ENZ-based phenomena can either be realized using the metamaterials or through the narrow waveguide channels [22]- [25]. It has recently been shown that by using the property of the ENZ structure, the sensitivity of planar dielectric sensors can be substantially improved in comparison to other conventional SIW sensors [24].…”
Section: Introductionmentioning
confidence: 99%
“…Most NZ structures proposed so far exploit behaviour of the TE10 propagation mode around its cut-off [5][6][7] which limits their application in planar circuits. Nevertheless, in [8][9] it has been recently demonstrated that NZ propagation can also be achieved in quasi-TEM structures, i.e.…”
Section: Introductionmentioning
confidence: 99%